A multi-agent architecture for lamb supply chain. (9th December 2014) - Mishra, Nishikant; Morris, Wyn; Singh, Akshit; McGuire, Steve
Small and medium size farming firms are unaware of the modern production system adjustments available to improve efficiency in lamb production and the lamb supply chain. These factors have collectively led to many serious issues confronting the sheep industry such as the bullwhip effect, quality of carcass not meeting the specifications of abattoirs, retailers, etc. This paper is postulating a multi-agent scheme for the lamb supply chain, which addresses above-mentioned issues facilitating a feedback system. This scheme involves various autonomous agents having their unique roles and responsibilities at different stages in the lamb supply chain to make it more efficient and customer focused. This scheme will lead to profit maximisation for the farmer, abattoir, and customers enabling maximum utilisation of resources all along the lamb supply chain.